2015
DOI: 10.1007/s00706-015-1588-3
|View full text |Cite|
|
Sign up to set email alerts
|

Calculating entropies of alkaline earth metal molybdates

Abstract: The most reliable molar entropies of solid phases are calculated from low-temperature heat capacity values. In the case of alkaline earth metal molybdates these data had been measured until very recently only for MgMoO 4 (cr) and CaMoO 4 , powellite, at T [ 50 K. Consequently extrapolation of the heat capacity function to T = 0 K played and still plays an important role. With state of the art mathematical routines integrals can be included in the nonlinear fit of experimental data leading to the adjustable par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…It was already shown in Gamsjäger et al [ 13 ] that it is possible to extrapolate heat capacity values for temperatures below 50 K when experimental values are only available at higher temperatures by the Kelley–King approach [ 16 ]. It is demonstrated in this work that the low temperature heat capacity up to 300 K of very different compounds can be approximated by the Debye–Einstein integral fit, Eq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was already shown in Gamsjäger et al [ 13 ] that it is possible to extrapolate heat capacity values for temperatures below 50 K when experimental values are only available at higher temperatures by the Kelley–King approach [ 16 ]. It is demonstrated in this work that the low temperature heat capacity up to 300 K of very different compounds can be approximated by the Debye–Einstein integral fit, Eq.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the values of these fit coefficients might be strongly correlated. Extending the approach outlined in a previous paper by Gamsjäger et al [ 13 ], it is suggested to use a Debye–Einstein integral fit for the whole temperature range from almost absolute zero to 300 K. It is expected that a unified fitting approach of the heat capacities facilitates the assessment of the thermodynamic data bases.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear fuel wastes are immobilized in waste glasses via three steps: (1) they are dissolved in concentrated aqueous nitric acid; (2) uranium and plutonium are separated by a solvent extraction; (3) the remaining aqueous solution containing fission product elements, minor actinides (Np, Am, Cm) and structural materials is conditioned by calcining and the incorporation of dry material into borosilicate glass. 17) Generally, a waste glass with such a high level of nuclear waste is then enclosed by an artificial barrier composed of steel, cement and bentonite and is disposed underground. 17) However, direct contact between the nuclear waste glasses and ground water is assumed to be unavoidable due to the collapse of such an artificial barrier by unpredictable natural disasters such as the movements of the Earth's crust, followed by diffusion of radio-active contaminated underground water.…”
Section: Introductionmentioning
confidence: 99%
“…17) Generally, a waste glass with such a high level of nuclear waste is then enclosed by an artificial barrier composed of steel, cement and bentonite and is disposed underground. 17) However, direct contact between the nuclear waste glasses and ground water is assumed to be unavoidable due to the collapse of such an artificial barrier by unpredictable natural disasters such as the movements of the Earth's crust, followed by diffusion of radio-active contaminated underground water. The Organization for Economic Co-operation and Development (OECD) Nuclear Energy Agency (NEA) Thermochemical Database (TDB) project provides a database of thermodynamic values of different compounds that contain the most significant elements that are relevant for nuclear waste safety management.…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory, thermodynamic investigations for molybdenum related-substances have been carried out [2][3][4][5] as a part of the OECD/NEA TDB Mo Project. Molybdenum is generated as ssion product from uranium in the operating nuclear reactor.…”
Section: Introductionmentioning
confidence: 99%